How men and women learn about sex: multi-generational perspectives on insufficient preparedness and prevailing gender norms in Scotland. Issue 4 (3rd July 2020) - Patterson, Susan; McDaid, Lisa; Hunt, Kate; Hilton, Shona; Flowers, Paul; McMillan, Lesley; Milne, Dona; Lorimer, Karen
ABSTRACT: Attitudes towards sexual health and relationships are learned from a young age, and there is an ongoing need for innovative and comprehensive approaches to sex education that keep pace with rapidly changing contexts of people's lives. We used thematic analysis of data from two qualitative studies in Scotland to explore learning contexts from a multi-generational perspective, as well as the influence of different socio-cultural factors on provision, access to and experience of sex education. The importance, but inadequacy, of school as a source of learning, was a persistent theme over time. Participants' strategies to address perceived gaps in knowledge included experience, conversations, vicarious and online learning. Gender and age differences emerged, with younger participants more likely to go online for information, and prevailing gender norms shaping attitudes and behaviours across both study groups. Participants who identified as gay, lesbian or bisexual described feeling particularly unprepared for sex and relationships due to the narrow, heteronormative content received. Although schools continue to be a common source of information, it appears that they fail to equip young people for their post-school sexual life-course. We recommend the mandatory provision of comprehensive, positive, inclusive and skills-based learning to improve people's chances of forming and building healthy, positive relationships across the lifespan.